THERE IS NO DIFFERENCE OF SURGICAL SITE INFECTION BETWEEN SINGLE-DOSE AND MULTIPLE-DOSE OF PROPHYLAXIS ANTIBIOTIC IN OPEN APPENDECTOMY OF NON-PERFORATED ACUTE APPENDICITIS - Tiono, B.G.; Sudartana, K.; Widiana, R. (BALI MEDICAL JOURNAL, 2013)
Objective: Acute appendicitis is the most common surgical emergency encountered compared with other non-traumatic acute abdomens. Sanglah General Hospital recorded there were 470 cases of acute appendicitis in the year 2006. This study  aims to determine the effectiveness of a single-dose antibiotic prophylaxis in prevention of surgical site infection in open appendectomy of non-perforated acute appendicitis. Method : A single blind randomized controlled trial in 110 non-perforated acute appendicitis patients that underwent open appendectomy at Sanglah General Hospital emergency operating theatre from April to June 2012 was conducted. Cefazolin 1 g and Metronidazole 500 mg were administered intravenously prior operation. Samples were divided into two groups by permuted block. Following operation, the single-dose group was administered placebo, while the multiple-dose group received two additional doses of antibiotics. Surgical site infection (SSI) of both groups in every week for one month was evaluated. Surgical site infection was determined based on Hulton’s criteria. Risk of surgical site infection of both groups was analyzed with Relative Risk (chi-square). Results : In the single-dose group 49.1% were males and 50.9% were females with a mean age of 28.71 years old, and in the multiple-dose group 40% were males and 60% were females with a mean age of 29.07 years old. Risk of SSI in single-dose group was 7.3% and multiple-dose group was 5.5% with Relative Risk (RR) = 1.33% (95% CI RR: 0.31-5.68, p= 1.000). Conclusion: There is no difference of SSI risk between single and multiple-dose antibiotic prophylaxisinopen appendectomy of non-perforated acute appendicitis.
Keywords: Antibiotic prophylaxis, single-dose, multiple-dose, non-perforated acute appendicitis, open appendectomy, SSI.